The Effect of Education Level and Open Unemployment on Poverty in Banten Province from 2019 to 2023 - Suriandhi, Denny; Wonatta, Ferdinando Maikelenden (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
Poverty has always been an interesting issue in every study, especially when it is related to education level and open unemployment. This study aims to analyse the effect of education level and open unemployment on poverty in Banten Province for the period 2019–2023. The data used is secondary quantitative time series data obtained from the Banten Province Central Statistics Agency (BPS) and the Ministry of Education and Culture of the Republic of Indonesia (Kemendikbud) for the period 2019–2023. The regression model used is the multiple linear regression analysis method. Based on the results of the study, the level of education partially (t-test) has a significant effect on poverty, with a t-count value greater than the t-table (3.134 > 271.2), and open unemployment partially (t-test) has a substantial impact on poverty with a t-count value greater than the t-table (2.155 < 271.2). However, simultaneously (F-test), these two variables together have a significant effect on poverty with a calculated F-value greater than the table F-value (55.114 > 3.25).